Soil Management for Sustainable Agriculture and Ecosystem Services - Piccini, Chiara; Francaviglia, Rosa (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue includes 14 papers by authors from Italy, USA, Egypt, Brazil, Russia, Indonesia, Czech Republic, China, Lithuania, the Netherlands, and Greece, dealing with several topics. The spatial distribution of soil organic carbon is useful for improving crop productivity and assessing the effect of agronomic management on crops and soil. Two interpolation methods and remotely sensed images were used in two papers. Other papers dealed with the use of zeolite-rich tuff in olive growing to reduce mineral fertilization, tested the effectiveness of green manure crops in providing nutrients and supplementing traditional fertilizers, and proposed composted sewage sludge as a source of micronutrients for crops. Since soil-borne diseases worsen the fertility, other authors studied the bacteria in the rhizosphere of saffron. Mapping and modeling soil suitability and capability under intensive land use in drylands with multivariate analysis was the topic of another paper, as was the evaluation of forest patches for preserving water regulation in tropical landscapes. Other findings regard agricultural conservation practices that reinforced the small water cycle and the comparison of deep-rooted vegetal covers for stabilizing slopes or repairing shallow landslides. Moreover, industrial solid waste can be a liming material to reduce soil acidification, increase crop productivity or amend soil; low-peat mixtures are able to provide C sequestration, climate regulation, and functional diversity services, while low-intensity management of high mountains can preserve seed-rich habitats for farmland avifauna.